The Influence of Store Atmosphere and Price on Purchasing Decisions Through Purchasing Interest as an Intervening Variable (Case Study on Consumers of ART.I Coffee and Space Bogor) - Asmin, Erny Amriani; Khoerunnisa, Salma Siti; Yulianingsih (MultiTech Publisher, 2024)
This research aims to determine the direct influence, indirect influence, and influence of total store atmosphere and price on purchasing decisions through purchasing interest. as an intervening variable. The population in this study were consumers of ART.I Coffee and Space Bogor. The number of samples used was 100 respondents using the purposive sampling method. Data analysis used descriptive and associative methods, path analysis using the IBM SPSS version 25.00 program. The research results show that store atmosphere and price have a positive and significant effect on buying interest, store atmosphere and price have a positive and significant effect on purchasing decisions, buying interest has an influence on purchasing decisions, buying interest is able to mediate store atmosphere and price on purchasing decisions.